GAMBARAN PERILAKU SEKS PRANIKAH REMAJA - Dwi Haryanti; Latifah Alkhasanah; Yulia Susanti (Jurnal Manajemen Asuhan Keperawatan, 2018)
Introduction: Adolescents are the next generation of the nation that will be the pride of the nation. Sexuality problems in adolescents must be considered because adolescence is a period of searching for self-identity, both individually and socially in the community. Irregularities in vulnerable sexual behavior occur at this time, which has an impact on physical and mental health in adolescents. The purpose of this study is to describes the role of premarital sex in adolescents. Methodology: Research with descriptive design uses a survey approach. The study population was adolescents living in kaliwungu sub-districts. A sample of 315 teenagers with a simple random sampling technique. The research instrument used a premarital sex structured questionnaire. The results showed the majority of teens 272 (86.3%) had poor premarital sex behavior and 43 (13.7%) adolescents had premarital sexual behavior in the bad category. Discussion: Pediatric nurses are expected to increase their role both promotively and preventively to overcome the problem of adolescent sexual behavior. Subsequent research to further examine psychological and social factors that influence adolescent premarital sex behavior.